Development of defatted cashew nut (Anacardium Occidentale Linn.) - Ang, Mary Sally Jane; Magluyan, Virginia B. (1985)
Cashew nut kernels were defatted using a mechanical press. Treatment of nuts with four different flavors were evaluated according to acceptability of the final product. Treatment with 20% sugar yielded the best product. Fat content of the defatted sample, fresh sample and roasted, defatted sample was determined. Results showed that there was resorption of oil during the roasting operation. Developments of fat deterioration was traced using the TBA test. Results showed that fat deterioration in the fresh sample was in an advanced state compared to that of the defatted sample.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Cashew nut